Pharmacokinetic modeling analysis of cilostazol and its active metabolites (OPC-13015 and OPC-13213) after multiple oral doses of cilostazol in healthy Korean volunteers. (3rd March 2020) - Cui, Ailing; Kim, Yo Han; Ghim, Jong-Lyul; Ah Jung, Jin; Cho, Sang-Heon; Choe, Sangmin; Choi, Hee Youn; Bae, Kyun-Seop; Lim, Hyeong-Seok
Abstract: Cilostazol is a selective inhibitor of phosphodiesterase III (PDE III), which is prescribed for patients with peripheral arterial disease, especially intermittent claudication. The purpose of the study was to investigate the pharmacokinetic (PK) of cilostazol and its metabolites on the immediate (IR) formulation of cilostazol in healthy Korean male volunteers by population PK modeling analysis implemented using NONMEM software. A 2 × 2 crossover study comparing multiple oral doses of IR and SR formulations of cilostazol were conducted. Serial plasma concentrations of cilostazol and its active metabolites were used in this analysis. The PK was best depicted by one-compartment model, with absorption kinetics of cilostazol having mixed first- and zero-order kinetics with a time delay at the beginning of absorption. The introduction of interoccasion variabilities into zero-order (D1), first-order (Ka), and relative bioavailability (F1) significantly improved the model fit, and total body water (TBW) was identified as a significant covariate positively affecting the clearance of cilostazol. The model validation suggested that the model constructed in this study predicted the plasma concentration of cilostazol and its two active metabolites reasonably well. The PK model we developed explored the PK characteristics of cilostazol in Korean male subjects, and may be useful for identifying optimal individual dosing regimens of cilostazol.